Genres and writing styles in the Press. Development and taxonomic variants - Mejia Chiang, César (2012)
One of the key factors in the maturation of modern Journalism, during the 20th century, has been the evolution of Journalism Genres, especially in the Press. Their domain allowed the appropriately diffusion of data, opinions and analysis into informative, opinion and interpretative texts that respected different styles, but also complementary, if one takesVinto account the overall content of a publication. Within Latin American Journalism, this intention has resulted in tripartite classifications. Currently, the Press interrelates with the new communication platforms (contained in the changing spectrum of Digital Journalism) that constantly used multimedia Internet resources, the immediacy of virtual social networks and the Microblogging. Within this scenario, Journalism Genders take a new importance in Print Media (newspapers, supplements, journalistic magazines, among others), setting up a methodology that safeguards professional ethics, helping journalists in the composition of substantial texts with appealing narrative, product of rigorous research, as well as specialized and multidisciplinary approach in line with the demands of the 21st century.